Poly(vinyl alcohol)‐methacrylate with CRGD peptide: A photocurable biocompatible hydrogel. (22nd November 2021) - Goldvaser, Michael; Epstein, Eyal; Rosen, Osnat; Jayson, Avital; Natan, Niva; Ben‐Shalom, Tal; Saphier, Sigal; Katalan, Shahaf; Shoseyov, Oded
Abstract: Polyvinyl alcohol (PVA)‐based hydrogels are promising biomaterials for tissue engineering printing applications. However, one of their main disadvantages is their inability to support cell attachment, which is a critical feature for the preparation of biological scaffolds. The goal of this study was to develop a printable, cell‐supportive PVA‐based bioink with tunable mechanical properties, without using animal‐derived polymers which potentially harbor human pathogens. An ultraviolet light (UV) curable PVA‐methacrylate (PVA‐MA) polymer mixed with Cys‐Arg‐Gly‐Asp (CRGD) peptide was developed. This peptide holds the integrin receptor binding sequence – RGD, that can enhance cell attachment. The additional cysteine was designed to enable its thiol binding under UV to methacrylate groups of the UV curable PVA‐MA. Vero cell, as an adherent cell model was used to assess the hydrogel's cell adhesion. It was found that the PVA‐MA‐CRGD formula enables the preparation of hydrogels with excellent cell attachment and had even shown superior cell attachment properties relative to added gelatin. Adding hyaluronic acid (HA) as a rheologic modulator enabled the printing of this new formula. Our overall data demonstrates the applicability of this mixture as a bioink for soft tissue engineering such as skin, adipose, liver or kidney tissue.